Serious adverse drug events related to non‐investigational drugs in academic clinical trials: another source of safety data for risk assessment?. (13th July 2016) - Olivier, Pascale; Gimbert, Anne; Colin, Anne‐Laurène; Salvo, Francesco; Becker, Madlyne; Marty, Valérie; Montastruc, Jean‐Louis; Petitpain, Nadine
Abstract : Aims: Sponsors of clinical trials have to analyze serious adverse events (SAEs). Both sponsors and investigators determine the relationship between the investigational medicinal product, the investigational device or procedure and SAEs. SAEs related to another cause, such as a non‐investigational medicinal product (NIMP), do not have clear pharmacovigilance reporting requirements. The aim of this study was to evaluate the amount and the nature of NIMP‐related SAEs recorded by three French academic sponsors and to propose pharmacovigilance requirements for these cases. Methods: This was a retrospective descriptive study including all cases of NIMP‐related SAEs occurring in clinical trials and reported to three academic sponsors between January 2009 and October 2014. Results: Among 5870 cases of SAEs, 300 (5%) were related to a NIMP in 50 clinical trials. Involved NIMPs were mainly antithrombotics, cytostatics and immunosuppressants. Some of these drugs were currently followed by a risk management plan (e.g. rivoxaban). The most frequent NIMP‐related SAEs were neurological, gastrointestinal and infectious disorders. Seven NIMP‐related SAEs were known as 'rare' or 'very rare' and two were 'unlabelled'. Conclusions: As far as we know, this is the first study to focus about NIMP‐related SAEs occurring in clinical trials. This work highlights the potential high quality source of safety data via NIMP‐related SAE collection. Globally, we propose that NIMP‐related SAEs occurring in clinical trials should systematically be notified to the pharmacovigilance system of the concerned country. Clearer procedures of interactions between safety units of academic sponsors and pharmacovigilance systems are needed to allow an effective recording of NIMP‐related SAEs.